Emerging Trends in Skin Anti-Photoaging by Lactic Acid Bacteria: A Focus on Postbiotics - Xiangji Jin; Trang Thi Minh Nguyen; Eun-Ji Yi; Qiwen Zheng; Se-Jig Park; Gyeong-Seon Yi; Su-Jin Yang; Mi-Ju Kim; Tae-Hoo Yi (Chemistry)
Background: Reflecting the increasing interest and research on living a healthy life as society ages, there has been a surge in attention and studies on photodamage. Probiotics have been studied for their ability to enhance skin integrity and provide protection from ultraviolet radiation (UVR). However, despite this, extensive research has revealed various issues and side effects, prompting increased interest in alternative options that can effectively and safely protect the skin. We focused on postbiotics as a promising solution for photodamage, aiming to demonstrate their potential as a safe and stable alternative to probiotics. Methods: We investigated papers on “skin aging” or “photoaging” and “probiotics” or “postbiotics” from 2013 to 2023 using the Web of Science, PubMed, and Scopus. Additionally, we compared and analyzed publications, authors, countries, keywords, and citations using the VOS viewer program. Results: According to our search results, the majority of papers on photodamage and probiotics were published in PubMed, with the United States leading in publication volume among countries. The most common keywords were “photodamage” and “skin”. The most cited paper recorded 470 citations. Furthermore, upon focused analysis of five papers on postbiotics and photodamage, postbiotics demonstrated preventive and protective effects against skin photodamage. Conclusions: Postbiotics for photodamage show potential as a safe and stable alternative to probiotics. However, research on postbiotics and photodamage remains limited, and additional studies and long-term tracking are essential to substantiate our claims.